2021
DOI: 10.3390/ani11102761
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Anthelmintic Resistance in Gastrointestinal Nematodes in Goats in Romania

Abstract: Currently, there are three classes of anthelmintics most commonly used in small ruminants: the benzimidazoles (BZs), macrocyclic lactones (MLs) and cholinergic agonists (especially levamisole; LEV). The widespread use of those products has led to the emergence of drug-resistant parasite strains which represents a serious threat to the livestock industry. In the present study, we describe for the first time a case of resistance to anthelmintics in goats in Romania. The study was carried out in 2021 in a dairy g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The cross-sectional study conducted by Mickiewicz et al 9 revealed the presence of AR to BZ, ML, and LEV on Polish goat farms, in which the resistance is widespread to BZ and ML, while the resistance to LEV is at a low level. Potârniche et al 2 also reported the resistance of gastrointestinal nematodes against MLs and BZs, in goats in Romania, which is the first report in the country. In addition, isolated reports revealed the occurrence of helminth resistance to the most recent classes of anthelmintics (for instance, Haemonchus contortus has developed resistance to monepantel, C, and an aminoacetonitrile derivative).…”
Section: Anthelmintic Resistance and Its Mechanismmentioning
confidence: 89%
See 2 more Smart Citations
“…The cross-sectional study conducted by Mickiewicz et al 9 revealed the presence of AR to BZ, ML, and LEV on Polish goat farms, in which the resistance is widespread to BZ and ML, while the resistance to LEV is at a low level. Potârniche et al 2 also reported the resistance of gastrointestinal nematodes against MLs and BZs, in goats in Romania, which is the first report in the country. In addition, isolated reports revealed the occurrence of helminth resistance to the most recent classes of anthelmintics (for instance, Haemonchus contortus has developed resistance to monepantel, C, and an aminoacetonitrile derivative).…”
Section: Anthelmintic Resistance and Its Mechanismmentioning
confidence: 89%
“…Sadly, application of anthelmintic drugs in an intensive way has led to a serious and dramatic level of anthelmintic resistance (AR), principally in cattle, sheep, goat, and equine gastrointestinal nematodes. 2 The increasing development of AR in parasites of livestock is threatening animal health and production worldwide. 3 Currently, there are three classes of anthelmintics most commonly used in small ruminants: the benzimidazoles (BZs), macrocyclic lactones (MLs) and cholinergic agonists (especially levamisole; LEV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the long-term sustainability of routine anthelmintic treatment is challenged by accelerating development of drug resistance in small ruminant parasites ( 6 , 7 ). GIT parasites have been shown to develop resistance to anthelmintic drugs following repeated use of the same anthelmintic over time, particularly for certain parasite species and drug classes such as benzimidazoles ( 8 ). Over time, these resistant organisms will dominate the parasite population and jeopardize efforts to control worm burden ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Routine anthelmintic treatment of small ruminants to control gastrointestinal tract (GIT) parasites is a recommended and accepted management practice to maintain and improve animal health and performance. However, the long-term sustainability of routine anthelmintic treatment is challenged by accelerating development of drug resistance in small ruminant parasites (6,7). GIT parasites have been shown to develop resistance to anthelmintic drugs following repeated use of the same anthelmintic over time, particularly for certain parasite species and drug classes such as benzimidazoles (8).…”
Section: Introductionmentioning
confidence: 99%